Hubungan Tingkat Pendidikan Dan Pekerjaan Dengan Ketepatan Ibu Dalam Memenuhi Jadwal Imunisasi Dasar Pada Bayi Di Wilayah Kerja Puskesmas Liang Anggang Tahun 2015 - Ermas Estiyana; Dian Rustina; Suaibahtul Aslamiah (Jurnal Kesehatan Indonesia, 2016)
Based on the constitution no. 36 in 2009 on Health in subsection 130 and 132, that are fully immunized is the government's obligation to provide as well as infant and child rights for Indonesia to obtain it. Based on data obtained from Liang Anggang Health Center Banjarbaru in 2014, from infant immunization coverage of 306 infants cumulative targets in 2014, immunized HB0 (93.1%), BCG (83.0%), DPT 1 / HB1 (84.5%), DPT 3 / HB3 (83.2%), Polio 1 (83%), Polio 4 (83.2%) and measles (84.2%). While the target of the complete basic immunization coverage is HB0 Banjarbaru health office (80%), BCG (95%), DPT/HB1 (95%), DPT / HB3 (90%), Polio1 (95%), Polio4 (90%) and measles (90%). The purpose of this study was to determine the correlation between level of education and occupation with mothers accuracy in fulfilling the basic immunization schedule in infants in the working area Liang Anggang Health Centers in 2015. This study is analytic survey research using cross sectional approach to the design of Chi square test. Sample were taken as many as 75 people using random sampling techniques. Results show the mother's education with basic education level of 30 people (40%), maternal employment status is not working as many as 45 people (60%), mother accuracy in meeting imunsasi schedule there are 53 people (70.7%). There was a corellation between maternal education to the fulfilling the basic immunization schedule in infants Liang Anggang Health Center working area 2015 by using the Chi-square test p value obtained (0,026) <α (0,05), and there was no corellation between maternal occupation with accuracy to fulfilling the basic immunization schedule in infants by using the Chi-square test p value obtained (0.379)> α (0,05). Expected to parents in order to increase knowledge about the importance of the provision of basic immunization of infants and improve compliance mother in immunization.